Total work and gender: Facts and possible explanations - Michael Burda; Daniel S. Hamermesh; Philippe Weil (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
Time-diary data from 27 countries show a negative relationship between real GDP per capita and female-male differences in total work time-work for pay and work at home. In rich non-Catholic countries on four continents men and women do about the same average amount of total work. Survey results demonstrate, however, that labor economists, macroeconomists, sociologists and the general public believe that women work more. The widespread average equality does not arise from gender differences in the price of time, from intra-family bargaining or from spousal complementarity. Several theories, including ones based on social norms, might explain these findings and are consistent with cross-national evidence from the World Values Surveys and sets of microeconomic data from Australia and Germany.
Keywords: J22; J16; D13; 330; time use; gender differences; household production; paid work; Arbeitszeit; Hausarbeit; Geschlecht; Zeitverwendung; Welt